Review on the allelopathic potential of the Euphorbiaceae family (Revista Brasileira Multidisciplinar, 2025)
The Euphorbiaceae family, comprising approximately 300 genera and 8,000 species, is renowned for its global diversity and the abundant presence of bioactive compounds with varied chemical compositions. An integrative review was conducted, encompassing scientific literature from Google Scholar (n=323), SciELO (n=1), and Web of Science (n=9), totaling 326 reviewed articles, spanning from 1983 to 2023. After applying inclusion and exclusion criteria, nine studies were included in the review. The analysis revealed the diversity of allelochemical compounds present in Euphorbiaceae species, with a particular focus on the genus Croton, which was studied with two specific species. These compounds exhibited inhibitory effects, suggesting a negative impact on the growth and development of other plants. The review also highlighted the scarcity of research conducted under natural conditions and emphasized the need to integrate bioassays with studies in plant chemistry. The results underscore the importance of understanding the complexities of allelopathy within the Euphorbiaceae family, providing valuable insights for potential applications in sustainable agriculture and pest control.
Keywords: allelochemicals; allelopathic activity; Euphorbiaceae; Metabolism